Tricuspid annuloplasty versus a conservative approach in patients with functional tricuspid regurgitation undergoing left-sided heart valve surgery: A study-level meta-analysis. (1st August 2017) - Pagnesi, Matteo; Montalto, Claudio; Mangieri, Antonio; Agricola, Eustachio; Puri, Rishi; Chiarito, Mauro; Ancona, Marco B.; Regazzoli, Damiano; Testa, Luca; De Bonis, Michele; Moat, Neil E.; Rodés-Cabau, Josep; et al.
Abstract: Background: Tricuspid valve (TV) repair at the time of left-sided valve surgery is indicated in patients with either severe functional tricuspid regurgitation (TR) or mild-to-moderate TR with coexistent tricuspid annular dilation or right heart failure. We assessed the benefits of a concomitant TV repair strategy during left-sided surgical valve interventions, focusing on mortality and echocardiographic TR-related outcomes. Methods: A meta-analysis was performed of studies reporting outcomes of patients who underwent left-sided (mitral and/or aortic) valve surgery with or without concomitant TV repair. Primary endpoints were all-cause and cardiac-related mortality; secondary endpoints were the presence of more-than-moderate TR, TR progression, and TR severity grade. All endpoints were evaluated at the longest available follow-up. Results: Fifteen studies were included for a total of 2840 patients. TV repair at the time of left-sided valve surgery was associated with a significantly lower risk of cardiac-related mortality (odds ratio [OR] 0.38; 95% confidence interval [CI]: 0.25–0.58; p < 0.001), with a trend towards a lower risk of all-cause mortality (OR 0.57; 95% CI: 0.32–1.05; p = 0.07) at a mean weighted follow-up of 6 years. The presence of more-than-moderate TR (OR 0.19; 95% CI: 0.12–0.30; p < 0.001), TR progression (OR 0.03; 95% CI: 0.01–0.05; p < 0.001), and TR grade (standardized mean difference − 1.11; 95% CI: − 1.57 to − 0.65; p < 0.001) were significantly lower in the TV repair group at a mean weighted follow-up of 4.7 years. Conclusions: A concomitant TV repair strategy during left-sided valve surgery is associated with a reduction in cardiac-related mortality and improved echocardiographic TR outcomes at follow-up.